Financial Comfort Zone and the Academic Learning Ethos of KIP-Kuliah Scholarship Recipients: A Phenomenological Study in the Perspective of Islamic Values - A Mukhsin Irfangi; Pubita Sasti Fintani; Muhammad Hanif Abdillah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the effect of the financial comfort zone on the learning discipline of college students receiving the KIP-Kuliah scholarship. The financial comfort zone is a psychological condition where students feel secure due to full tuition coverage and monthly stipends, which potentially triggers a moral hazard in the form of academic passivity. This study employs a qualitative approach with a phenomenological method. Data were gathered through in-depth interviews and observation of KIP-Kuliah recipients whose class attendance fell below 75%. The results indicate that a stable financial comfort zone contributes to a decline in learning discipline when not accompanied by rigid institutional monitoring or strong intrinsic motivation. The guarantee of